2017
DOI: 10.18203/2349-2902.isj20175897
|View full text |Cite
|
Sign up to set email alerts
|

Stapled hemorrhoidopexy versus Milligan-Morgan haemorrhoidectomy: a paradigm shift in the management of 3rd and 4th degree hemorrhoids

Abstract: Background: Hemorrhoids being a common anorectal problem with its well known morbidity and complications is treated since long by conservative measures, injection sclerotherapy or rubber banding for 1st and 2nd degree and by open Miligan Morgan hemorrhoidectomy or closed Fergusson hemorrhoidectomy for 3rd and 4th degree. However, since 1998, the adoption of Stapled Hemorrhoidopexy has proved over time to be a better alternative in terms of lesser postoperative complication and an overall patient satisfaction.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Our results were in line with that of Ganio et al, where they reported a mean hospital stay of 1 day [13] . Panigrahi et al reported a mean hospital stay of 2.08 days [5] . The slight differences noted in hospital stay with different studies is the reflection of differences in hospital discharge protocols and the way in which the length of hospital stay is determined in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in line with that of Ganio et al, where they reported a mean hospital stay of 1 day [13] . Panigrahi et al reported a mean hospital stay of 2.08 days [5] . The slight differences noted in hospital stay with different studies is the reflection of differences in hospital discharge protocols and the way in which the length of hospital stay is determined in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…While considering insignificantly intrusive hemorrhoidopexy strategies for overseeing progressed hemorrhoidal sickness, Stapled Hemorrhoidopexy (SH) stays a protected and solid choice for patients with chiefly third and fourth degree hemorrhoids [44]. SH has the upsides of hemorrhoidopexy methods with respect to decreased postoperative agony, shorter emergency clinic remain, and early come back to work, however this must be adjusted to the greater expense of the technique and the conceivable, regardless of whether uncommon, genuine complications [45].…”
Section: Hemorrhoidopexy:rubber Band Ligation Versus Manual Hemorrhoidopexy In Treatmentmentioning
confidence: 99%